Exploring learning strategies used by Jordanian University EFL learners in argumentative writing tasks: the role of gender and proficiency - Almashour, Mohamad; Davies, Amanda (Frontiers in Education, 2023)
This study investigates learning strategies in argumentative writing tasks among 60 English as a Foreign Language (EFL) university students, classified as proficient or less-proficient writers based on essay scores. Data was collected through a validated questionnaire assessing six categories of learning strategies: affective, metacognitive, social, compensatory, cognitive, and memory. Findings suggest female students utilize affective strategies more than males, but proficiency level does not significantly influence strategy choice. The results underline the need for explicit instruction in learning strategies as current student usage appears rudimentary. The study emphasizes the role of learning strategies in enhancing EFL writing performance, and future research could explore specific learning strategies in different language learning tasks.